UMPSA Researchers Successfully Develop Spiritual Intelligence Knowledge Module To Empower MUIP Preachers - Rohana, Hamzah (UMPSA, 2024)
KUALA LUMPUR, 23 July 2024 - A team of researchers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) successfully developed a Spiritual Intelligence Knowledge Module for preachers of the Pahang Islamic Religious and Malay Customs Council (MUIP).